Unnatural Female Deaths within Seven Years of Marital Life: An Autopsy based Study - Jeeveswararao Bagadi1, Srinivasulu Pothireddy2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Unnatural female deaths pose a major challenge for society. The study was conducted on 644 unnatural female deaths during the calendar years from 2008 to 2012, in the Department of Forensic Medicine, Andhra Medical College. Women less than 29 years of age group, in the first three years of their marital life were the major victims in our study. Improving women literacy may give employment and there by economical independency of women.